The intensity of ground motion from future earthquakes in the Mentawai islands, Sumatra - Xu, Da. (2010)
Records from historical sea-level change based on the observation of corals on the west coast of Sumatra and velocity vectors derived from GPS data indicated the possible rupture of Mentawai Segment in the near future. The rupture will create giant earthquake with magnitude of around 8.8. The seismic wave and possible tsunami may cause severe property damage and large amount of casualties if no proper preparation is done. Hence, the objective of this project was to exam the effect of this future Sumatra earthquake towards the structure stability in Sumatra area under current design code. By knowing this, a better design can be carried out for the new projects and proper reinforcement can be done for present structures. With the help of the potential slip graph of Mentawai patch from Kerry Sieh et al.’s paper on “Science” and crust information fetched from Crust 2.0 global crustal model, a close simulation of the future rupture of Mentawai patch can be carried out by using FORTRAN program developed by Prof. Kazuki Kohketsu. Ground motion in terms of velocity time series can be generated. With these ground motion, deformation as a function of natural period for single degree of freedom system can be calculated using Newmark’s method. Response spectrums for the cities of interest were plotted out and compared with elastic design spectrum based on Indonesian design code. After that, interpolations were obtained from the ground motion and response spectrum data. All above steps were achieved by using matlab programming. The result showed that near source cities like Padang may experience structure yielding for median to high-rise buildings; further cities like Jakarta and Medan will have little effect from this earthquake; Singapore may have potential risk with median to high-rise buildings, especially for HDB buildings due to lack of seismic design considerations. This report will demonstrate the theory, procedure, result and analysis of this simulation, as well as the discussion about the inaccuracy raised in the process of simulation. Report will also give recommendations of solution and suggestions for further research.